The Progress and Prospect of Tunable Organic Molecules for Organic Lithium-Ion Batteries - Xu, Danying; Liang, Minxia; Qi, Shuo; Sun, Weiwei; Lv, Li-Ping; Du, Fei-Hu; Wang, Baofeng; Chen, Shuangqiang; Wang, Yong; Yu, Yan (ACS nano, 2021)
Compared to inorganic electrodes, organic materials are regarded as promising electrodes for lithium-ion batteries (LIBs) due to the attractive advantages of light elements, molecular-level structural design, fast electron/ion transferring, favorable environmental impacts, and flexible feature, etc. Not only specific capacities but also working potentials of organic electrodes are reasonably tuned by polymerization, electron-donating/withdrawing groups, and multifunctional groups as well as conductive additives, which have attracted intensive attention. However, organic LIBs (OLIBs) are also facing challenges on capacity loss, side reactions, electrode dissolution, low electronic conductivity, and short cycle life, etc. Many strategies have been applied to tackle those challenges, and many inspiring results have been achieved in the last few decades. In this review, we have introduced the basic concepts of LIBs and OLIBs, followed by the typical cathode and anode materials with various physicochemical properties, redox reaction mechanisms, and evolutions of functional groups. Typical charge–discharge behaviors and molecular structures of organic electrodes are displayed. Moreover, effective strategies on addressing problems of organic electrodes are summarized to give some guidance on the synthesis of optimized organic electrodes for practical applications of OLIBs.